2017
DOI: 10.1007/s13770-017-0097-3
|View full text |Cite|
|
Sign up to set email alerts
|

Endogenous Stem Cells in Homeostasis and Aging

Abstract: In almost all human tissues and organs, adult stem cells or tissue stem cells are present in a unique location, the so-called stem cell niche or its equivalent, continuously replenishing functional differentiated cells. Those endogenous stem cells can be expanded for cell therapeutics using ex vivo cell culture or recalled for tissue repair in situ through cell trafficking and homing. In the aging process, inefficiency in the endogenous stem cell-mediated healing mechanism can emerge from a variety of impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 174 publications
(210 reference statements)
0
12
0
Order By: Relevance
“…Osteoarthritis is a degenerative disease that strongly correlates with age [38,39]. Mesenchymal stem/progenitor cells derived from synovial joint tissues exhibit a superior chondrogenic ability compared with those derived from non-joint tissues [1,40,41]; thus, they represent the best choice for the regeneration and repair of cartilage [40].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis is a degenerative disease that strongly correlates with age [38,39]. Mesenchymal stem/progenitor cells derived from synovial joint tissues exhibit a superior chondrogenic ability compared with those derived from non-joint tissues [1,40,41]; thus, they represent the best choice for the regeneration and repair of cartilage [40].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have shown that mesenchymal stem cells (MSCs) yield a favorable therapeutic bene t for GVHD and most clinical trials have used MSCs [5,14], nevertheless, the controversy about their safety and e cacy still remains. Although, BM is the main source of MSCs, the use of BM-MSCs is not always acceptable because of the invasive harvesting procedure, besides, the number of BMSCs declines with increasing age [15,16]. Placenta tissue-derived MSCs have the advantage of being readily available and easy to collect from a waste product, which has been reported to contain a population of multipotent stem cells exhibiting characteristics of MSCs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, exogenous or endogenous stem cells have been shown to contribute to cardiac tissue regeneration by either differentiation into the vascular cell types or by paracrine mechanisms [ 42–45 ]. We also observed significant recruitment of CD29-positive MSCs in SP patch, IGF-1C patch and IGF-1C/SP patch-treated groups than that of the saline and patch-only groups.…”
Section: Discussionmentioning
confidence: 99%